Create of the Agglomeration Railway in Wrocław with the use of new cross-city sections - Mariusz Korzeń; Igor Gisterek (Przegląd Komunikacyjny)
Abstract: The paper is closely related to the article "Concept of the cross-city railway route in Wrocław to create the LRT system" (PK 2/2021, p. 6-10) [2] and is a continuation of the topic related to create of the Agglomeration Railway system in Wrocław with particular emphasis on city traffic service. The study focused on the creation of an efficiently functioning system, the key element of which is the cross-city section. It has been pointed out that the route of the cross-city section will be the main factor that will determine the level of use of railways in journeys within the city limits. Therefore, the current condition of the Wrocław Railway Junction was analyzed in terms of adapting it to the needs of LRT, focusing primarily on the best accessibility of travelers to system. Places where new stops should be created to increase the attractiveness of agglomeration transport have been indicated. In the following points, three variants of system are proposed depending on the route of the cross- city route. In the summary, the most advantageous variant was indicated and the use of hybrid sections (road-rail) was proposed as one of the solutions that could improve the transport network in the city in the near future. Keywords: Agglomeration railway; Wrocław; Cross – city route